Geography, Race/Ethnicity, and Physical Activity Among Men in the United States - Sohn, Elizabeth Kelley (Am J Mens Health, 2017)
Engaging in regular physical activity reduces one’s risk of chronic disease, stroke, cardiovascular disease, and some forms of cancer. These preventive benefits associated with physical activity are of particular importance for men, who have shorter life expectancy and experience higher rates of chronic diseases as compared to women. Studies at the community and national levels have found that social and environmental factors are important determinants of men’s physical activity, but little is known about how regional influences affect physical activity behaviors among men. The objective of this study is to examine the association between geographic region and physical activity among men in the United States, and to determine if there are racial/ethnic differences in physical activity within these geographic regions. Cross-sectional data from men who participated the 2000 to 2010 National Health Interview Survey (N = 327,556) was used. The primary outcome in this study was whether or not men had engaged in sufficient physical activity to receive health benefits, defined as meeting the 2008 Physical Activity Guidelines for Americans. Race/ethnicity and geographic region were the primary independent variables. Within every region, Hispanic and Asian men had lower odds of engaging in sufficient physical activity compared to white men. Within the Northeast, South, and West, black men had lower odds of engaging in sufficient physical activity compared to white men. The key findings indicate that the odds of engaging in sufficient physical activity among men differ significantly between geographic regions and within regions by race/ethnicity.